Long-term effect of contact lens wear: A citation network study. Issue 1 (February 2022) - Sánchez-Tena, Miguel Ángel; Martinez-Perez, Clara; Villa-Collar, Cesar; Alvarez-Peregrina, Cristina
Abstract: Background: Contact lenses can cause complications in 2/3 of the total population, but in most cases, they are mild and easy to manage. However, most of the studies are short-term. The aim of the study was to analyze the publications on the long-term effects of contact lens wear to understand the current research landscape through the analysis of dating networks as well as determining the different research areas and the most cited publications. Methods: The Web of Science database was used to perform the publication search, looking for the terms "Long-term" AND "contact lens wear" within the period between 1977 and January 2021. The CitNetExplorer and CiteSpace software were then used to conduct the publication analysis. To obtain the graphics, the VOSviewer software was used. Results: A total of 721 publications were found with 2999 citations generated within the network. The year 2010 was singled out as a "key year", considering the number of publications that emerged in that year and increase in adaptations of contact lens worldwide. The most widely cited publication was "Effects of long-term extended contact lens wear on the human cornea", an article by Holden et al., which was published in 1985. By using the clustering function, we were able to establish three clusters that encompassed the different research areas within this field: morphological changes, the loss of corneal sensitivity, tear film characteristics and longitudinal changes in ocular physiology. Conclusions: The main research topic in this field focuses on the morphological changes that take place in the corneal endothelial cell layer.